2023
DOI: 10.1186/s12909-023-04414-x
|View full text |Cite
|
Sign up to set email alerts
|

A virtual training program for improving cultural competence among academic nurse educators

Abstract: Background Everyday, nursing students interact with culturally diverse clients. Nursing education recognizes that cultural competence is a necessary outcome of nursing programs. Nurse educators expect all nursing students to provide culturally congruent care to multicultural clients. Therefore, nurse educators must be culturally competent in order to prepare culturally competent nursing students for clinical practice. This study aimed to evaluate the effect of virtual training program on the cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…The qualitative findings of the study revealed that after undergoing lectures with standardized patient simulation, students experienced a decrease in anxiety when interacting with culturally diverse patients, and their comfort levels in patient interactions improved [ 5 ]. These findings align with similar studies conducted in Iran, which also demonstrated the effect of virtual cultural care training on the cultural competence of undergraduate students [ 10 ], postgraduate students [ 16 ], and nursing professors [ 26 ]. These studies suggest that given the current globalized world and the increasing prevalence of medical tourism, nursing and midwifery schools should prioritize cultural care education at all educational levels.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The qualitative findings of the study revealed that after undergoing lectures with standardized patient simulation, students experienced a decrease in anxiety when interacting with culturally diverse patients, and their comfort levels in patient interactions improved [ 5 ]. These findings align with similar studies conducted in Iran, which also demonstrated the effect of virtual cultural care training on the cultural competence of undergraduate students [ 10 ], postgraduate students [ 16 ], and nursing professors [ 26 ]. These studies suggest that given the current globalized world and the increasing prevalence of medical tourism, nursing and midwifery schools should prioritize cultural care education at all educational levels.…”
Section: Discussionsupporting
confidence: 91%
“…This systematic instructional model proved to be effective in guiding the development process of the mobile app-based cultural care training program. In contrast, previous studies that developed cultural care training programs did not adhere to any instructional models and often lacked reporting on their development processes [ 5 , 16 , 26 , 34 36 ].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Studies conducted in Iran have also supported the effectiveness of virtual cultural care training in enhancing the cultural competence of undergraduate students [ 22 ], postgraduate students [ 2 ], and nurse educators [ 21 ]. A review study (2019) focused on fostering cultural competence in nursing education through a values-based learning approach.…”
Section: Discussionmentioning
confidence: 99%